Association of Helicobacter pylori related chronic atrophic gastritis and gastric cancer risk: a literature review - Zhang, Zefeng; Chen, Sitong; Li, Shudan; Zheng, Yadan; Mai, Lifei; Zhang, Xiaoguang (Frontiers in Medicine, 2025)
Chronic atrophic gastritis (CAG) is considered to be closely related to Helicobacter pylori (H. pylori) infection and characterized by the atrophy and/or intestinal metaplasia (IM) of the gastric mucosa in pathology. CAG is often regarded as the precancerous lesion of gastric cancer and H. pylori infection stimulates the development of atrophy and IM and the progression of gastric cancer through the persistent effect acting on the gastric mucosa, including releasing inflammatory factors such as Interleukin-8(IL-8). From the molecular biology perspective, growing evidence shows that H. pylori probably induce the expression of NF-κB, miR-204, miR-27a, hnRNPA2B1, and JARID1B, which play crucial roles in the progression of CAG into gastric cancer. In addition, H. pylori can increase Epstein-Barr virus (EBV) infection, and the co-infection will jointly increase gastric cancer risk. Furthermore, H. pylori induces cellular senescence and promotes atrophy progression and finally increases the gastric cancer risk. This review aims to explore the carcinogenic mechanisms of H. pylori related CAG in order to provide theoretical foundations for the pathogenesis mechanism and early detection and prevention of gastric cancer.